Drosophila P element-enhanced transfection in mammalian cells. - Clough, D W (1985)
We constructed a gene transfer vector containing the herpes simplex virus type 1 thymidine kinase (TK) gene flanked by Drosophila P element terminal repeats (W. R. Engels, Annu. Rev. Genet. 17:315-344). This vector was introduced into mouse LTK- cells and enhanced the frequency of stable transformation to the TK+ phenotype by approximately 50-fold relative to a similar plasmid lacking the P element terminal repeats.